EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE CIRC (COOPERATIVE INTEGRATED READING AND COMPOTITION) PADA KEMAMPUAN PEMECAHAN MASALAH - Binti Anisaul Khasanah (Universitas Muhammadiyah Pringsewu, 2016)
didikan Matematika, STKIP Muhammadiyah Pringsewu Email: binti_anisa@ymail.com Abstract The purpose of this study is to know the effectiveness of cooperative learning CIRC'S type to trouble-shooting ability on subject rectangular. The subject of this study was all of the students on VII.A class of SMP N Satu Atap 2 Negerikaton in the academic year of 2014-2015. Method of this study was descriptive analysis. Researcher used observation sheet they were teacher's ability sheet, activity's student sheet, respond's student sheet, then to get students' learning achievement were used essay. Learning indicator that focused on ability aspect, student activity and student response is more than 75%, therefore it will increase. Base on the data, teacher's ability was 78,23%, students' activity was 76,84%, students' response was 78,48%, base on percentage it will impact learning achievement that reached, based on essay result means that student's percentage result was success and gets above Minimum Completeness Criteria is 77,78% therefore studying result are good, those four indicators learning effectiveness goal is more than 75%, it means that learning model purpose CIRC to mathematics learning on rectangular material is effective to trouble-shooting ability on subject rectangular. Keywords: Cooperative Integrated Reading and Compotition, effectiveness in learning